2021
DOI: 10.1093/plankt/fbaa061
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between a planktivorous fish and planktonic microcrustaceans mediated by the biomass of aquatic macrophytes

Abstract: Habitat complexity is recognized to mediate predator–prey relationships by offering refuge or not. We investigated the availability of planktonic microcrustaceans and the diet of a planktivorous fish (Hyphessobrycon eques) at different levels (low, intermediate and high) of aquatic macrophyte biomass. Sampling was carried out in a river with low flow speed, located in a Neotropical floodplain. We collected fish and microcrustaceans in macrophyte stands with variations in biomass. There were no differences in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…This observation aligned with Brito et al [48] who reported that the high occurrence of zooplankton species within floodplain regions can be attributed, in part, to the substantial presence of extensive aquatic macrophyte cover. Submerged or free-floating macrophytes foster an elevated species diversity by expanding the available colonization area, enhancing the availability of food resources, and providing a refuge from predation [49][50][51]. Prior investigations have also demonstrated that habitat intricacy, brought about by aquatic macrophytes, functions as a predictive factor for biodiversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation aligned with Brito et al [48] who reported that the high occurrence of zooplankton species within floodplain regions can be attributed, in part, to the substantial presence of extensive aquatic macrophyte cover. Submerged or free-floating macrophytes foster an elevated species diversity by expanding the available colonization area, enhancing the availability of food resources, and providing a refuge from predation [49][50][51]. Prior investigations have also demonstrated that habitat intricacy, brought about by aquatic macrophytes, functions as a predictive factor for biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…Prior investigations have also demonstrated that habitat intricacy, brought about by aquatic macrophytes, functions as a predictive factor for biodiversity. This complexity contributes to species richness and facilitates the expansion of a more extensive genetic reservoir within the zooplankton community [46,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…They also provide substrates for algae and invertebrates attachment (dos Santos et al 2013, Cunha et al 2012), but they attract predators, which further increase the diversity within macrophyte stands (Thomaz & Cunha 2010). Numerous studies retrieved by our search addressed the role of macrophytes as a refuge for zooplankton (e.g., dos , Quirino et al 2021 and macroinvertebrates (e.g., Padial et al 2009), demonstrating how macrophytes can influence predator-prey interactions. Macrophytes provide an efficient physical and visual barrier against predators, decreasing predation rates and allowing different organisms to successfully explore these habitats (Pelicice et al 2008, Dibble & Pelicice 2010.…”
Section: Effects Of Macrophytes On the Environment And Other Communitiesmentioning
confidence: 99%
“…Submerged macrophytes also affect the spatial distribution of organisms as they provide spawning substrate, nursery areas, refuge against predators, and food (Dibble et al, 1996;Quirino, de Mello, et al, 2021;Slade et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in shallow lakes, macrophytes play a critical role by stabilising the sediment, assimilating nutrients, and modifying the trophic structure, all contributing to maintain a clear water state (Jeppesen et al, 1998; Thomaz, 2021). Submerged macrophytes also affect the spatial distribution of organisms as they provide spawning substrate, nursery areas, refuge against predators, and food (Dibble et al, 1996; Quirino, de Mello, et al, 2021; Slade et al, 2005).…”
Section: Introductionmentioning
confidence: 99%